Control of Mechatronics Systems: COMES Toolbox - Demirel, Burak; Gu¨venç, Levent (ASMEDC, 2010)
An interactive software tool based on MATLAB to analyze and design controllers for mechatronic systems is presented in this paper. This toolbox called COMES is a graphical user interface (GUI) to routines for four different control approaches: classical control (lead, lag, PID etc.), preview control, model regulator control and repetitive control. These control approaches have all found widespread use in the practical implementation of controllers for mechatronic systems. The aim is to design a user-friendly toolbox with a well designed graphical user interface (GUI), which hides all calculations from the user as much as possible. Thus, the user can focus on the design and analysis phases through the graphical displays rather than being burdened by the complicated calculations that are involved. The effectiveness of the use of this MATLAB-based toolbox was demonstrated by carrying out some design and simulation studies for several position control applications available in the literature.